The Influence of Oral Administration of Red Dragon Fruit Peels Extract (Hylocereus polyrhizus) on Increasing High Density Lipoprotein in Male White Rats (Rattus norvegicus) Hypercholesterolemia - Ahmad Thoriqul Firdaus; Gandul Atik Yuliani; Tri Wahyu Suprayogi; Nusdianto Triakoso; Eduardus Bimo Aksono Herupradoto; Nanik Hidayatik (Journal of Applied Veterinary Science And Technology, 2023)
Background: Hypercholesterolemia is one of the most common diseases in the world, with cholesterol levels exceeding normal levels. Hypercholesterolemia can cause various systemic disorders in the body. One of the signs is by decreasing HDL (High-Density Lipoprotein) cholesterol levels. Dragon fruit peel contains many ingredients, such as vitamin B3 (niacin), vitamin C, flavonoids, anthocyanins, and other minerals that can affect the increase in HDL production and reduce total cholesterol levels. Purpose: To know the effect of red dragon fruit peel extract (Hylocereus polyrhizus)on increasing levels of High-Density Lipoprotein (HDL) in male rats (Rattus norvegicus) hypercholesterolemia. Methods: Male rats were made hypercholesterolemic using a mixture of lard (3 ml) and egg yolk (1 g) for 14 days orally. 20 hypercholesterolemic male rats were further divided into 5 treatment groups and given dragon fruit peel extract therapy with different treatments, namely T0 negative control (CMC-Na 1% + aquadest), T1 positive control (Simvastatin 0.0013 mg/200 g BW), T2, T3 and T4 (each 100, 150, 200 mg/kg BW red dragon fruit peel extract) for 14 days orally.  Blood serum was taken on day 36 and tested in the laboratory using a chemical analyzer machine; then the data were analyzed using the univariant multiple way one-way ANOVA statistical test with a significant difference (p>0.05). Results: The P4 treatment group has an effective dose (200 mg/kg BW) to increase high-density lipoprotein (HDL) levels, while the P3 treatment group (dose 150 mg/kg BW) is less effective but can still have an effect. Conclusion: This research showed that red dragon fruit peel extract could increase HDL (High-Density Lipoprotein) cholesterol levels with an effective 200 mg/kg BW dose.